(untitled) (Research, Society and Development, 2021)
This study analyzed the socioeconomic profile and knowledge about oral health of high-risk pregnant women attended at the Lauro Wanderley University Hospital (HULW) of the Federal University of Paraíba (UFPB). This is an observational, descriptive, cross-sectional and quantitative study, which used the Epi Info program version 7.2.4 to perform statistical data analysis. The study was composed of 51 high-risk pregnant women assisted at the HULW of UFPB, from the application of a structured questionnaire, divided into two stages; the first with 5 questions that addressed the socioeconomic profile of patients and the second with 7 questions related to knowledge and care about oral health during pregnancy. As part of the results found, in relation to age group, 28 pregnant women (54.90%) were between 24 and 33 years old; 45 (88,24%) had up to 2 minimum wages as family income; 51 (100%) pregnant women know what caries is, but 33 (64.7%) believe that caries is not transmitted by saliva. Regarding the use of anesthetics and radiographs during pregnancy, 31 (60.78%) and 32 (62.74%), respectively, of the patients believe that it is not possible to perform such procedures during pregnancy. It is concluded that the knowledge of high-risk pregnant women about oral health care during pregnancy is limited, generating divergences and gaps in responses, predominantly low schooling and income level.